El dantisme de Manuel de Montoliu - Ardolino, Francesco (Caplletra. Revista Internacional de Filologia, 2007)
In the year 1903 Manuel de Montoliu published the first Catalan version, in prose and poetry, of La Vida Nova, which meant an important stage within the history of pre-Raphaelitism and modernism in Catalonia. In this article the first Dantesque influences in the poetic production of the translator will be detected, the stage of preparation and of presentation of the text will be analysed and, finally, the article will study the progression that the exegesis of Dante’s work determines in Montoliu’s thought. This global vision will leave a redimensionated image of the critic which concerns the originality of his positions, and it will be demonstrated that the interpretations on the figure of Beatrice will lead him into focusing his interest in the most doctrinal aspects of the Divine comedy.